Agentes infecciosos causadores de diarreia e sua associação com idade em cães - Gizzi, Aline Baumann Rocha; Braga, Karina Francini; Leutenegger, Christian; Albino, Daphine Maciel; Marcondes, Mary [UNESP]; Stedile, Rafael; Biondo, Alexander Welker; Oliveira, Simone Tostes (My University, 2013)
A real-time PCR (qPCR) panel was performed in 104 diarrheic faeces samples of dogs. The panel included the detection of Canine Distemper Virus, Canine Enteric Coronavirus (CEC), Canine Parvovirus 2 (CP2), Clostridium perfringens enterotoxin A gene (CPEA), Cryptosporidium spp, Giardia spp and Salmonella spp. Among the samples, 43/104 were from 0-1 year-old dogs, 36/104 from 1-8 years-old dogs and 25/104 from dogs over 8 years-old. Statistical difference was observed between age and the pathogens CP2, Giardia spp. and CEC, being more prevalent among the 0-1 year-old dogs. There was a high significant difference between age and coinfection (P<0,0001), being more prevalent among the 0-1 year-old dogs. In conclusion, the presence of infectious pathogens was detected in diarrheic dogs of all ages, highlighting the importance of investigating these pathogens regardless of the age of the dog.
Infectious agents causing diarrhea and its association to age in dogs
Keywords: Age; Coinfection; Dog; Enteritis; Real time PCR